Ripples of Hope: How Ordinary People Resist Repression Without Violence - Press, Robert M. (Protest and Social Movements, 2015)
In Ripples of Hope, Robert M. Press tells the stories of mothers, students, teachers, journalists, attorneys, and many others who courageously stood up for freedom and human rights against repressive rulers - and who helped bring about change through primarily nonviolent means. Global in application and focusing on Kenya, Liberia and Sierra Leone, this tribute to the strength of the human spirit also breaks new ground in social movement theories, showing how people on their own or in small groups can make a difference.